Identifying Shadow Economic Activities in the Real Estate Sector - Storonyanska Iryna Z.; Dub Andrii R. (Problemi Ekonomiki, 2020)
The shadow economy is an integral part of the functioning of the national economy of almost any country in the world. In Ukraine, the size of the shadow economy, despite a positive downward trend over the past five years, remains high. In the real estate sector, the extent of shadow activities significantly exceeds the corresponding indicator for the national economy as a whole. The aim of the study is to identify the shadow component and its size in the real estate sector, as a basis for further research and development of measures for tackling shadow real estate transactions. Using direct and indirect research methods, shadow activities in the real estate sector are detected, their heterogeneity being pointed out. The complexity of clear identification of the shadow component, due to the fact that unlawful (criminal) actions of certain entities can take place within the framework of legal activity and vice versa, is noted. The breaking down of shadow real estate transactions into informal, hidden (“gray”) and illegal (criminal or “black”) is carried out. The indicator of the size of the shadow component in the real estate sector published by the Ministry for Development of Economy, Trade and Agriculture of Ukraine is critically evaluated. The study justifies the thesis of understatement of the indicator resulting from a high volume of unreported activities of individual entrepreneurs engaged in the real estate sector and transactions involving residential leasing carried out by individuals who are not registered and do not declare received income, as well as a large size of the criminal (“black”) component in the real estate sector. It is noted that the consequences of shadow real estate transactions are not only a decrease in budget revenues due to non-payment of taxes and fees but also the risks of non-fulfillment or improper fulfillment of verbal agreements by the parties, especially as concerns residential leasing.